The 3′ region of the ZPA regulatory sequence (ZRS) is required for activity and contains a critical E-box - Ball, Kathryn F.; Manu, Stephen; Underhill, Abbie K.; Kim, Jeanyoung; Britton, Jessica C.; Rudd, Sarah R.; Malone, Madison M.; Amoah, Japhet; Cooper, Allen; Pira, Charmaine; Oberg, Kerby C. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDuring development, Hand2 and Hoxd13 transcription factors (TFs) regulate Sonic hedgehog (Shh) expression in the zone of polarizing activity (ZPA) in the distal posterior limb mesoderm. The ZPA regulatory sequence (ZRS) is a conserved, limb-specific enhancer that controls Shh expression. The ZRS can be divided into 5′, central, and 3′ subdomains, each with an E-box site that can bind basic helix-loop-helix (bHLH) TFs like Hand2. In addition, two Hoxd13 sites are present in the 5′ and central subdomains. Hand2 purportedly binds the ZRS through the central E-box, and both Hand2 and Hoxd13 have been shown to activate the ZRS in vitro. We hypothesized that the central E-box was required for activity, while the other E-boxes and Hoxd13 sites localize ZRS activity to the distal posterior limb mesoderm.MethodsTo identify the functional role of each subdomain, we generated three ZRS fragments (5′, central, and 3′) and combined fragment constructs to test subdomain collective contributions. Additionally, we disrupted the five binding sites, alone or in concert, using site-directed mutagenesis. All ZRS constructs were cloned into a GFP reporter and evaluated in an in vivo chicken limb bioassay. We validated our findings using select ZRS constructs in transgenic mice.ResultsWe found that the 3′ fragment was necessary for ZRS activity, while the 5′ and central fragments had no activity alone or when combined. However, combining the 3′ fragment with the 5′ fragment restored robust activity. Further, mutation of all five binding sites markedly reduced ZRS activity. Reinstating each of the Hoxd13 sites restored focal activity, while restoring the 5′ and central E-boxes had little effect. However, the 3′ E-box proved sufficient for robust activity even in the absence of the other four binding sites.ConclusionOur data indicate that the ZRS 3′, not the central, subdomain is necessary for activity and contains the 3′ E-box that Hand2 likely uses to induce Shh expression, while the 5′ and central E-boxes appear to be inhibitory. Our data also suggest that the Hoxd13 binding sites promote localized activity within the ZPA.